GAMBARAN PENGETAHUAN DAN SIKAP IBU TENTANG PELAKSANAAN TOILET TRAINING PADA ANAK USIA 1-3 TAHUN DI WILAYAH KERJA POSYANDU KELURAHAN SUKAMAJU KECAMATAN SAIL KOTA PEKANBARU - Rina Ovie Denada; Elda Nazriati; Fifia Chandra (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
ABSTRACTOne of the important aspects in development of children in toddler age is toilet training. The right knowledge and attitude of mother’s are really needed in toilet training. The purposes of this study were to describe mother’s knowledge and attitude about implementation of toilet training in children aged 1-3 years. This study was conducted at Posyandu (Integrated Health Service Center) Working Area, Sukamaju Village, Sail District, Pekanbaru City. This study was done by using descriptive method and cross sectional approach. The sample consisted of 56 mothers of toddlers. This data was collected by doing an interview which using a questionnaire. The result of this research showed that majority of mothers have adequate knowledge (73,2%), neutral attitude (67,9%) and already implemented toilet training (67,9%). Most children (44,7%) in this study were toilet trained before the age of 18 months and the most characteristic of mothers who implemented toilet training were mothers age 20-35 years (64,3%), senior high school (39,3%), housewife (57,1%) and having ≤2 child (62,5%). This study has been shown that boys (39,3%) were toilet trained have higher frequency than girls. Most mothers who implemented toilet training have adequate knowledge (48,2%) and neutral attitude (46,4%).Keywords : Knowledge, attitude, implementation, toilet training, toddler